Comparing RT-WiFi and HCCA approaches to handle real-time traffic in open communication environments - Robson Costa (2012)
In this paper we make a comparative assessment betweenthe RT-WiFi and HCCA approaches to handle realtimetraffic in IEEE 802.11 networks operating in opencommunication environments. The main focus will be onthe assessment of the admission control mechanism proposedfor the RT-WiFi upper layer, that is based on a nonpreemptiveEDF scheduling algorithm combined with amechanism that measures the blockage times on mediumaccess of real-time stations due to retransmissions and delays.The goal is to achieve a good compromise betweenmedium utilization and timeliness. This proposal is comparedwith HCCA, and the results show that RT-WiFi offersa significantly better behavior in what concerns themaximum number of admitted streams.